A “geograficidade” das formas simbólicas: o santuário de Fátima da Serra Grande em análise - Christian Dennys Monteiro de Oliveira; José Arilson Xavier de Souza (Confins)
The “geograficity” of symbolic forms: The Sanctuary of Fatima da Sierra Grande in analysis.This paper discusses the geographical basis of symbolic forms, choosing the culture as an essential element for such research. The Sanctuary of Fátima da Serra Grande, located in St. Benedict city, Northern of the Ceará State, is analyzed in a geographical and phenomenological perspective, considering it as a symbolic form of tourist attraction. The article considers the concept of geographic originally proposed by Eric Dardel, as fundamental for thinking the relationship between motivation and appreciation of the devotees in search of new Catholic shrines. Then, a recovery is made as large sanctuaries influenced the cultural geography of this small and dynamic center of pilgrimage has been developing in northeastern Brazil. At the end of the paper presents the characteristics expressing Fátima da Serra Grande as a symbolic model of Catholicism Marian conciliator of traditions and innovations and manager of a religious tourism under the leadership of the regional church.